2012
DOI: 10.2527/jas.2011-3949
|View full text |Cite
|
Sign up to set email alerts
|

Acute heat stress impairs performance parameters and induces mild intestinal enteritis in broiler chickens: Role of acute hypothalamic-pituitary-adrenal axis activation1

Abstract: Studies on the environmental consequences of stress are relevant for economic and animal welfare reasons. We recently reported that long-term heat stressors (31 ± 1°C and 36 ± 1°C for 10 h/d) applied to broiler chickens (Gallus gallus domesticus) from d 35 to 42 of life increased serum corticosterone concentrations, decreased performance variables and the macrophage oxidative burst, and produced mild, multifocal acute enteritis. Being cognizant of the relevance of acute heat stress on tropical and subtropical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
98
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 178 publications
(113 citation statements)
references
References 45 publications
8
98
0
7
Order By: Relevance
“…The results obtained reinforce the hypothesis that the decreased performance observed in stressed broiler chickens might be related to alterations in the HPA axis function via corticosterone release (Shini & Kaiser, 2008;Shini et al, 2009;Quinteiro-Filho et al, 2010, 2012a, 2012b. Moreover, the observed intestinal inflammation could lead to a decrease in nutritional absorption because of the presence of intestinal lesions and because of sickness-related behaviour by release of certain interleukins (i.e.…”
Section: Discussionsupporting
confidence: 74%
“…The results obtained reinforce the hypothesis that the decreased performance observed in stressed broiler chickens might be related to alterations in the HPA axis function via corticosterone release (Shini & Kaiser, 2008;Shini et al, 2009;Quinteiro-Filho et al, 2010, 2012a, 2012b. Moreover, the observed intestinal inflammation could lead to a decrease in nutritional absorption because of the presence of intestinal lesions and because of sickness-related behaviour by release of certain interleukins (i.e.…”
Section: Discussionsupporting
confidence: 74%
“…Mashaly et al (2004) reported that heat stress not only adversely affected the performance, but also inhibited the immune function in chickens. Results of this study showed that high ambient temperature suppressed growth performance through reduction in FI, which is in agreement with the literature (Geraert et al, 1996;Mashaly et al, 2004;Quinteiro-Filho et al, 2012). Results of the present study showed a 10.3% decline in FI of birds kept under 35°C compared to those kept under 25°C.…”
Section: Growth Performancesupporting
confidence: 82%
“…IgA, IgY, and IgM titers were determined using ELISA commercial kits (Bethyl Laboratories, Montgomery, TX, USA) as described by Quintero Filho et al (2012). The kit precision limit was 15.62 ng/mL, with a detection range of 15.62-1000 ng/mL.…”
Section: Methodsmentioning
confidence: 99%